E-SeniArca on IoT Platform in Education of Sculpture Arts - Nuraini Mohd Rani; Che Zalina Zulkifli; Mohd Fauzi Sedon; Abdul Aziz Zalay (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: In education, by using any media method is one of the most important elements of an educational institution, especially in order to make a consistent learning session. It also can give the two ways communication between teachers and students. Based on E-SeniArca learning tool, it will provide a new way to deliver the information with more effectively. By the lack of references material of sculpture arts topics, it was difficult for students to learn and perform their achievement. In fact, students can purpose to design, transfer, construct and test the effectiveness of the E-SeniArca learning tool in sculpture topics. Design: The methods are used to the production of E-SeniArca learning tool on technology are the ADDIE Model. Findings: The actual image depiction of the sculpture arts through the images is shown to clearly explain the shape of arc that have in sculpture concepts. Research limitations: This study has developed an application of 12 flip cards for scanning by E-SeniArca learning tools to generate 3D images on each of the different picture cards. Practical implications: Much of the software used to produce this learning tool has been able to attract students to learn the basics of sculpture arts. Paper type: International Journal of Entrepreneurship and Business Development (IJEBD)